Real Coded Genetic Algorithm (RCGA): a new RCGA mutator called Scale Truncated Pareto Mutation - Lim, Siew Mooi; Sulaiman, Md. Nasir; Md. Sultan, Abu Bakar; Mustapha, Norwati; Tejo, Bimo Ario (Asian Research Publishing Network (A R P N), 2014)
This paper presents a comparison in the performance analysis between a newly developed mutation operator called Scaled Truncated Pareto Mutation (STPM) and an existing mutation operator called Log Logistic Mutation (LLM). STPM is used with Laplace Crossover (LX) taken from literature to form a new generational RCGA called LX-STPM. The performance of LX-STPM is compared with an existing RCGA called LX-LLM on a set of 10 benchmark global optimization test problems based on a few performance criterions to investigate the reliability, efficiency, accuracy and quality of solutions of both optimization algorithms. The final outcomes show that LX-STPM is far superior than LX-LLM at all aspects.